The Effect of Moving Target Drills on Futsal Passing Accuracy at SMPN 5 Seluma - Exsel Milanda; Roni Syaputra; Oetari Lismana (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aimed to determine the effect of zig-zag running training on the dribbling skills of SSB PGM U14–U16 soccer players. The background of this study was based on the players' relatively low dribbling ability, particularly in terms of agility, ball control, and the ability to change direction while dribbling. This research employed an experimental method using a One Group Pretest–Posttest Design. The population consisted of 35 SSB PGM U14–U16 players, while the sample included 20 players selected through a purposive sampling technique. The research instrument was a dribbling skill test measured by the time taken to complete the dribbling course in seconds. Data were collected through a pretest, the implementation of zig-zag running training as the treatment, and a posttest. Data analysis was conducted using normality tests, homogeneity tests, and a paired sample t-test at a significance level of 0.05. The results showed that the data were normally distributed and homogeneous. Hypothesis testing revealed a t-count value of 7.826 and a t-table value of 1.729, indicating that t-count > t-table. These findings demonstrate that zig-zag running training has a significant effect on improving the dribbling skills of SSB PGM U14–U16 soccer players. Furthermore, the average posttest score was better than the pretest score, indicating an improvement in dribbling ability after the training program. Therefore, it can be concluded that zig-zag running training is effective in enhancing the dribbling skills of U14–U16 soccer players.